DID MENDEL CHEAT? - Bokhari, Faraz Ahmed; Sami, Waqas (Journal of Ayub Medical College Abbottabad, 2007)
Who does not know Gregor Mendel? Mendel is considered to be the father of genetics. The often stated irony is that Mendel's work, at the time of presentation of his famous paper titled '˜Experiments in plant hybridization', was not taken seriously. It would be later, the year 1900, that a few botanists would '˜rediscover' Mendel's work and the field of genetics would find its place at the center of human curiosity. What Mendel might not have envisaged is that his scientific inferences would be questioned on scientific, and even moral grounds. The main arguments indicting Mendel and his work, started to brew when world renowned mathematician and statistician, R. A. Fisher, discovered peculiarities in Mendel's data. Fisher, who in the words of Anders Hald1 was a genius who almost single-handedly created the foundations for modern statistical science, while lecturing at Cambridge in 1911 quipped: It is interesting that Mendel's original results all fall within the limits of probable error; if his experiments were repeated the odds against getting such good results is about 16 to one. It may have been just luck; or it may be that the worthy German abbot, in his ignorance of probable error, unconsciously placed doubtful plants on the side which favored his hypothesis.